Study on Hydraulic Performances of a 3-Bladed Inducer Based on Different Numerical and Experimental Methods. (24th November 2016) - Fu, Yanxia; Fang, Yujiang; Yuan, Jiangping; Yuan, Shouqi; Pace, Giovanni; Dagostino, Luca
Abstract : The hydraulic performances of a 3-bladed inducer, designed at Alta, Pisa, Italy, are investigated both experimentally and numerically. The 3D numerical model developed in ANSYS CFX to simulate the flow through the inducer and different lengths of its inlet/outlet ducts is illustrated. The influence of the inlet/outlet boundary conditions, of the turbulence models, and of the location of inlet/outlet different pressure taps on the evaluation of the hydraulic performance of the inducer is analyzed. As expected, the predicted hydraulic performance of the inducer is significantly affected by the lengths of the inlet/outlet duct portions included in the computations, as well as by the turbulent flow model and the locations of the inlet/outlet pressure taps. It is slightly affected by the computational boundary conditions and better agreement with the test data obtained when adopting the k - ω turbulence model. From the point of the pressure tap locations, the pressure rise coefficient is much higher when the inlet/outlet static pressure taps were chosen in the same locations used in the experiments.